Degradation of dipyrone via advanced oxidation processes using a cerium nanostructured electrocatalyst material - Assumpção, M. H M T; Moraes, A.; De Souza, R. F B; Reis, R. M.; Rocha, R. S.; Gaubeur, I.; Calegaro, M. L.; Hammer, Peter [UNESP]; Lanza, M. R V; Santos, Mirian Cristina dos [UNESP] (Elsevier, 2013)
This work studied the degradation of dipyrone, via electrochemical processes and via electro-Fenton reaction using a 4% CeO2/C gas diffusion electrode (GDE) prepared via modified polymeric precursor method. This material was used to electrochemically generate H2O2 through oxygen reduction. The mean crystallite sizes estimated by the Scherrer equation for 4% CeO2/C were 4 nm for CeO2-x (0 4 4) and 5 nm for CeO2 (1 1 1) while using transmission electron microscopy (TEM) the mean nanoparticle size was 5.4 nm. X-ray photoelectron spectroscopy (XPS) measurements revealed nearly equal concentrations of Ce(III) and Ce(IV) species on carbon, which contained high oxygenated acid species like CO and OCO. Electrochemical degradation using Vulcan XC 72R carbon showed that the dipyrone was not removed during the two hour electrolysis in all applied potentials by electro-degradation. Besides, when the Fenton process was employed the degradation was much similar when using cerium catalysts but the mineralization reaches just to 50% at -1.1 V. However, using the CeO2/C GDE, in 20 min all of the dipyrone was degraded with 26% mineralization at -1.3 V and when the Fenton process was employed, all of the dipyrone was removed after 5 min with 57% mineralization at -1.1 V. Relative to Vulcan XC72R, ceria acts as an oxygen buffer leading to an increase in the local oxygen concentration, facilitating H2O2 formation and consequently improving the dipyrone degradation © 2013 Elsevier B.V. All rights reserved.
Keywords: Cerium oxide nanoparticles; Dipyrone degradation; Gas diffusion electrode; H2O2 electrogeneration; Advanced Oxidation Processes; Cerium oxide nanoparticle; Dipyrone; Electrochemical degradation; Electrogeneration; Gas diffusion electrodes; Nanostructured electrocatalysts; Transmission electron microscopy (TEM); Carbon; Cerium compounds; Diffusion in gases; Electrocatalysts; Electrolytic reduction; Mineralogy; Nanoparticles; Oxygen; Photoelectrons; Transmission electron microscopy; X ray photoelectron spectroscopy; Cerium